THE PERFORMANCE OF PSORIATIC ARTHRITIS CLASSIFICATION CRITERIA IN PSORIATIC ARTHRITIS IN TURKISH PATIENTS - Nas, K.; Karkucak, M.; Durmus, B.; Ulu, M. A.; Karatay, S.; Capkin, E.; Ozgocmen, S. (Clinical & Exper Rheumatology, 2012)
[Abstract Not Available]